2018
DOI: 10.1080/14708477.2018.1465069
|View full text |Cite
|
Sign up to set email alerts
|

Viewing CLIL through the eyes of former pupils: insights into foreign language and intercultural attitudes

Abstract: This article examines the long-term effects of CLIL on former pupils' foreign language and intercultural attitudes. The 24 participants, who received English-medium CLIL for nine years in the 1990s, were interviewed and the data analyzed using thematic analysis. The participants generally felt that CLIL had had a very positive effect on their target language attitudes. However, many considered that CLIL had affected negatively on their attitudes towards other foreign languages. The perceptions regarding the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
0
11
0
2
Order By: Relevance
“…This result is contradictory to studies on non-CLIL early language teaching that have found an early start resulting in a positive attitude towards languages in general (Muñoz and Singleton 2011). This suggests that in CLIL context, multilingualism should be explicitly acknowledged so that the CLIL language would not cast aside other foreign languages (see also Roiha and Sommier 2018). One solution is to offer a multitude of languages already at primary level.…”
Section: Implications and Conclusionmentioning
confidence: 77%
See 2 more Smart Citations
“…This result is contradictory to studies on non-CLIL early language teaching that have found an early start resulting in a positive attitude towards languages in general (Muñoz and Singleton 2011). This suggests that in CLIL context, multilingualism should be explicitly acknowledged so that the CLIL language would not cast aside other foreign languages (see also Roiha and Sommier 2018). One solution is to offer a multitude of languages already at primary level.…”
Section: Implications and Conclusionmentioning
confidence: 77%
“…The interviews lasted from 30 minutes to 79 minutes, the average being 48 minutes. The semi-structured interviews were based on broad themes which were given to the interviewees in advance in order for them to recollect aspects and experiences of their CLIL education (see Roiha and Sommier 2018). Despite the general outline, each interview was slightly different as the participants were given the opportunity to focus on the topics relevant to them and their individual life trajectories.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst others, Ortega-Martín, Hughes, and Madrid (2018) have conducted extensive research on the influence of political factors on bilingual CLIL programmes in Spain which confirms that such schemes do not attach enough importance to intercultural competence development or to language assistants. Moreover, Roiha and Sommier (2018) assert that the participants in their study (former CLIL students) "did not receive formal intercultural communication training during their CLIL education" (p. 12).…”
Section: European Parliament and Council Of The Europeanmentioning
confidence: 99%
“…One way to improve language skills, especially English, is to use these languages in learning (Brevik & Moe, 2012;Roiha & Sommier, 2018;Martínez Agudo, 2019;Deswila et al 2020). Learning that integrates content and language in learning is known as Integrated Learning and Content Learning (CLIL) (Dalton-Puffer, 2011;Baneges, 2012;Dale & Tanner, 2012;Coyle et al 2013).…”
Section: Introductionmentioning
confidence: 99%